13. The Mascot-Jefferson City Zinc District, Tennessee - Johnson Crawford; Alan H. Hoagland (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1968)
Zinc mining at Jefferson City began in 1854 with small scale production of oxidized ore from open pits. Significant production began in 1913 with the development of the Mascot Mine by the American Zinc Company. In 1965, four flotation mills were treating crude ore at the rate of about 12,000 tons per day and the Mascot-Jefferson City district currently is the largest zinc producing area in the United States. The producing mines, Mascot, Young, North Friends Station, New Market Zinc, Grasselli, Davis-Bible, Coy, and the Jefferson City, are 15 to 28 miles northeast of Knoxville in the Valley and Ridge physiographic province, an area of gentle relief lying between the more rugged Great Smoky Mountains and the Cumberland escarpment. The ore is strata bound, occurring essentially within a stratigraphic range of 200 feet in the Lower Kingsport and Upper Longview formations of Lower Ordovician age. In the lower strata of the mineralized section, the ore generally is found in coarsely crystalline elastic dolomite breccia containing silica and chert debris within a sequence of aphanitic limestones. The upper strata of the mineralized section are fine-grained primary dolomites that, in the ore zones, have been fragmented in mosaic patterns by solution collapse with the interfragmental space filled by white gangue dolomite and sphalerite. The mineralogy is unusually simple, sphalerite being the only important sulfide. Pyrite is very sparse. Dolomite gangue is abundant, silica was deposited in quite small amounts, calcite is minor, and fluorite and barite are very rare. The principal ore controlling structures are rubble breccia zones that were formed during the post-Lower Ordovician-pre-Middle Ordovician erosion interval by supergene solution as a phase of the development of a regional karst system of underground drainage that extended to' depths of at least 800 feet. The major Appalachian orogenic structures are post-ore and have been superimposed on the ore bodies. There is substantial evidence to support the current thinking of the writers that the ore deposits were formed at a depth not exc1~eding 800 feet.